Aquachloridobis(2-ethoxy-6-formylphenolato-κ(2) O (1),O (6))chromium(III) acetonitrile hemisolvate - Ghelenji, Safoora (International Union of Crystallography, 2011)
In the mononuclear complex molecule of the title compound, [Cr(C(9)H(9)O(3))(2)Cl(H(2)O)]·0.5CH(3)CN, the Cr(III) atom displays an elongated octahedral coordination geometry. The dihedral angle between the benzene rings is 12.27 (11)°. Adjacent complex molecules are linked into dimers by O—H⋯O hydrogen bonds, generating rings of R (1) (2)(6) and R (1) (2)(5) graph-set motifs, and by aromatic π–π stacking interactions, with a centroid–centroid distance of 3.812 (2) Å. The crystal packing is further stabilized by intermolecular C—H⋯N hydrogen bonds. The C and N atoms of the acetonitrile solvent molecule are located on a crystallographic twofold axis.